Dampak Debt to Equity Ratio (DER), Current Ratio (CR), dan Return on Asset (ROA) terhadap Harga Saham pada PT Kalbe Farma Tbk Periode 2019-2023 - Sinaga, Lusi Betricia (Asosiasi Dosen Akuntansi Indonesia, 2024)
This study aims to analyze the effect of Debt to Equity Ratio (DER), Current Ratio (CR), and Return on Assets (ROA) on the stock price of PT Kalbe Farma Tbk during the period 2019-2023. The research data is sourced from the company's annual reports and analyzed using multiple linear regression to evaluate the relationship between financial ratios and stock prices. The results show that DER and CR have a significant negative effect on stock prices, while ROA does not have a significant effect. These findings provide insights for company management and investors to pay more attention to debt management and liquidity inmaking financial decisions.